Sensitivity of physical parameterization of WRF model in urban climate simulation and Heat Island mitigation in a stable atmospheric condition (case study: Tehran and Alborz provinces) - fahimeh shakeri; gholamabbas Fallah ghalhari; hashem akbari; zahra hejazizadeh (تحقیقات کاربردی علوم جغرافیایی)
In this research, the sensitivity of the meteorological elements (such as mean temperature, relative humidity and wind speed) to different physical parameterizations in the numerical forecast model (WRF) was evaluated to simulate the climate of the city and adjust the Urban Heat Island of the study area.To study urban environmental issues, the Urban Canopy Model (UCM) was coupled to the WRF model. Several experiments were performed to achieve optimal configuration for simulation in the period from 18-21 August 2016 in the stable atmospheric conditions in summer. Selection of the most appropriate configuration with the least error is proposed as an appropriate setting for urban climate simulations and the study of Urban Heat Island (UHI). Increasing surface reflections to reduce UHI in the range was applied. Two indices of Root Mean Square Error (RMSE), and Mean Bias Error (MBE) were used to evaluate the predictive performance of the model and its corresponding observational values. The results showed that in the province of Tehran, in general, all configurations estimate the air temperature and wind speed less than real and relative humidity more than the actual value. In Alborz province, all configurations estimate the air temperature and wind speed more than real and relative humidity less than real value. By increasing the reflection of urban levels, the mean temperature of Tehran and Alborz provinces decreases 0.6 and 0.2 ° C, respectively. Wind speed, especially in urban areas, increases somewhat. We also see an increase in relative humidity (especially in urban areas) in the studied areas.